Alpine Treeline Dynamics and the Special Exposure Effect in the Hengduan Mountains - Zou, Fuyan; Tu, Chengyi; Liu, Dongmei; Yang, Chaoying; Wang, Wenli; Zhang, Zhiming (Frontiers in Plant Science, 2022)
Alpine treeline is highly sensitive to climate change, there is still a lack of relevant research on the relationship between treeline dynamics and climate change on a landscape scale.The rising speed of temperature in Hengduan Mountain area is much higher than the global average. Under this background, we extracted alpine treeline positions of Hengduan Mountain from high-resolution Google Earth images for three period (2000, 2010 and 2020), and analyzed the elevation patterns and dynamics of treeline positions. Based on the treeline position of 2020, a buffer zone of 300m is established as the treeline transition zone, and the change trend of the fraction vegetation cover (FVC) from 2000 to 2020 and its relationship with climate are also analyzed. The treeline elevation in Hengduan Mountain area was high in the middle but lower in surrounding areas. We found that, for the past 20 years, the treeline position doesn’t change significantly, but the 80.3% of FVC of the treeline areas are increased. The increase of the FVC on the east slope and south slope is positively correlated with temperature change, while the west slope and north slope are negatively correlated with precipitation. Due to regional climate warming, the restrictions on tree growth caused by low temperature and high precipitation have been alleviated to a great extent. The results also revealed a special exposure effect of alpine treeline in the Hengduan Mountain. Because of the lower treeline isotherm position caused by the monsoon climate, the treeline position on the south slope is lower than the other slope exposures. Our results confirm that the pattern and dynamics of alpine treeline in Hengduan Mountain are driven by the regional monsoon climate regime.